Effects of Plant Extracts on Controlling Seed Borne Fungi of Okra (Abelmoschus esculentus L. Moench) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted using farmers okra (Abelmoschus esculentus L. Moench) seeds in Seed Pathology Centre, Bangladesh Agricultural University, Mymensingh to determine the efficacy of plant extracts (garlic, allmanda, neem, ginger and biskathali extracts) and vigour index of seedling for controlling the seed-borne fungal diseases of okra. In the laboratory experiment, the prevalence of seed-borne fungi associated with farmers okra seed investigated by blotter method. The identified fungi species in the collected seeds were Colletotrichum dematium, Macrophomina phaseolina, Fusarium oxysporum, Aspergillus flavus, Aspergillus niger, Penicillium spp. and Rhizopus spp. The test seed materials were treated with garlic tablet, allmanda tablet @ 1:1 and 2:1 w/v and neem extract, ginger extract and biskathali extract @ 1:1 and 1:2 w/v for each to control pathogens with control treatment. The significantly highest germination (62.5%) and lowest incidence of pathogen (5.25%) were recorded in garlic tablet @ 2:1 w/v treated seeds. The okra seeds treated by garlic tablet @ 2:1 w/v was also showed the higher vigour index (545.60%) compare to untreated seed (423.40%).DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22212 J. Environ. Sci. & Natural Resources, 7(2): 85-88 2014